DAMPAK DEPRESIASI RUPIAH TERHADAP PERKEMBANGAN IMPOR INDONESIA - Amir Machmud (Quantitative Economics Journal, 2016)
This study aims to identify and analyze the impact of depreciation on the development of Indonesian imports. The method used in this study was a descriptive study with data collection through observation to the data issued by Bank Indonesia (BI) during the fourth quarter of 2012 - the second quarter of 2015.The collected data were then analyzed by quadrant analysis through growth andshare, as well as regression analysis. The results showed that the depreciation of the rupiah significantly negative effect on the development of imported goods inIndonesia, both consumer goods, raw and auxiliary materials, and capital goods. Inother words, the higher the value, the exchange rate declining demand for importedgoods as a whole.